Prevalensi hipertensi pada orang dewasa menengah dengan overweight di denpasar tahun 2018 - Komang Erdwin Wicaksana; I Wayan Surudarma; Desak Made Wihandani (DiscoverSys Inc., 2019)
Background: Hypertension is an increase in systolic and diastolic blood pressure that exceeds the normal limit. Overweight in middle-aged adults is caused by excessive amounts of fat cells due to excessive calorie intake early.Methods: This type of descriptive research is carried out by using a retrospective approach. Data collection starting from events that have occurred or are ongoing to do a description of general characteristics and specific variables of the study to answer the research objectives. Variables that have been recorded will be determined by the prevalence of hypertension and overweight. The subjects of the study were hypertensive patients in middle-aged with overweight based on data obtained from East Denpasar Puskesmas I. Sampling was done using a random sampling method.Results: The prevalence of hypertension in middle-aged adults with overweight in Denpasar in 2018 there were 36.1% of respondents with stage 1 hypertension and 18% of respondents with stage 2 hypertension, with the incidence of hypertension with overweight is highest in the age group 56 - 60 years, with a percentage of 62.5%.Conclusions: The number of hypertensive patients in middle-aged adults with overweight in women is higher than in men.Latar Belakang: Hipertensi adalah peningkatan tekanan darah systolic dan diastolic yang melewati batas normal. Overweight pada dewasa menengah disebabkan oleh jumlah sel lemak yang berlebihan karena pemberian kalori yang berlebihan sejak dini.Metode: Jenis penelitian ini adalah deskriptif dilakukan dengan menggunakan pendekatan retrospektif. Subyek penelitian adalah penderita hipertensi pada dewasa menengah dengan overweight berdasarkan data yang diperoleh dari Puskesmas I Denpasar Timur. Pengambilan sampel dilakukan dengan menggunakan metode random sampling.Hasil: Prevalensi hipertensi pada orang dewasa menengah dengan overweight di Denpasar tahun 2018 terdapat 36,1% responden dengan hipertensi stadium 1 dan 18% responden dengan hipertensi stadium 2, dengan angka kejadian hipertensi dengan overweight paling tinggi pada kelompok umur 56 – 60 tahun, dengan persentase sebesar 62,5%.Simpulan: Jumlah pasien hipertensi pada orang dewasa menengah dengan overweight pada wanita lebih tinggi dibandingkan pria.